Improvement of Qualitative and Quantitative Aspects of the Sports Performance of Young Players Through High Intensity Interval Training - Tiziana D'Isanto; Felice Di Domenico; Italo Sannicandro; Francesca D'Elia (OVS LLC, 2022)
Objective. One of the most widely used training methodologies in football is high intensity interval training (HIIT), which aims to improve performance through training sessions characterised by exercises that involve alternating percentage load intensity. In the literature, although there are studies that demonstrate the effectiveness of HIIT in improving quantitative aspects, i.e. different expressions of strength, there are not as many studies that attest to the same effectiveness in improving qualitative components, i.e. elements related to the precision of specific football gestures. The study purpose was to verify whether the application of a specific HIIT protocol for football over a given period of time can be equally effective in simultaneously improving the quantitative and precision components.  Materials and methods. The sample analysed consisted of 16 movement players from the ASD Nuova Antoniana sports club, aged between 14 and 15 years. The sample was subjected to a mesocycle of training lasting 8 weeks characterised by the HIIT methodology. Before and after this period, data were collected by means of a battery of tests aimed at assessing rapid, explosive, fast and resistant strength, and passing and shooting skills: the parameters relating to expressions of strength were assessed by means of quantitative tests specific to each parameter; passing and shooting skills were assessed by means of accuracy score tests (from 0 to 4 according to accuracy). Results. The results showed an improvement in all tested parameters (p ≤ 0.05). Therefore, the effectiveness of the protocol in improving football performance in terms of quantity and accuracy is confirmed. Conclusions. This study has increased knowledge of the effects of the HIIT protocol on the performance of young football players.